2017
DOI: 10.1111/conl.12415
|View full text |Cite
|
Sign up to set email alerts
|

Reserve Sizes Needed to Protect Coral Reef Fishes

Abstract: Marine reserves are a commonly applied conservation tool, but their size is often chosen based on considerations of socioeconomic rather than ecological impact. Here, we use a simple individual-based model together with the latest empirical information on home ranges, densities and schooling behaviour in 66 coral reef fishes to quantify the conservation effectiveness of various reserve sizes. We find that standard reserves with a diameter of 1-2 km can achieve partial protection (ࣙ50% of the maximum number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 41 publications
2
37
0
2
Order By: Relevance
“…Abesamis et al 2014). Our recommended marine reserve size to protect most fishes (C 10 km) is also consistent with previous studies (Green et al 2015;Krueck et al 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Abesamis et al 2014). Our recommended marine reserve size to protect most fishes (C 10 km) is also consistent with previous studies (Green et al 2015;Krueck et al 2018).…”
Section: Discussionsupporting
confidence: 90%
“…3 B ). Our study design meant that it was not possible to uncover the mechanisms responsible for this decline of ecological condition indicators within marine reserves along a gravity gradient, but this pattern of depletion is likely related to: ( i ) human impacts in the surrounding seascape (fishing, pollution, and so forth) affecting ecological processes (recruitment, feeding behavior, and so forth) within reserves ( 33 , 34 ); ( ii ) almost every marine reserve is likely to have some degree of poaching, even where compliance is considered high ( 20 , 35 ) and the cumulative impacts from occasional poaching events is probably higher in high-gravity situations; ( iii ) the life history of top predators, such as old age of reproduction and small clutch size for some (e.g., sharks), which makes then particularly susceptible to even mild levels of exploitation ( 36 ); and ( iv ) high-gravity marine reserves in our sample possibly being too young or too small to provide substantial conservation gains ( 11 , 37 ). We conducted a supplementary analysis to further examine this latter potential explanation.…”
mentioning
confidence: 99%
“…Thus, even small amounts of fishing in remote openly fished areas may be depleting top predators, which creates a large difference between low-gravity–fished areas and marine reserves. This difference may diminish along the gravity because top predators tend to have large home ranges ( 37 ), and there were only small reserves in high-gravity locations ( SI Appendix , Fig. S3 ), which may mean that existing high-gravity reserves are not likely big enough to support the large home ranges of many predators ( 37 , 47 ).…”
mentioning
confidence: 99%
“…These declines in commercially valuable size classes both inside and outside of protected areas could indicate potential infractions into the protected sites, such as at the Batasan MPA where the site guardhouse was noted to have been damaged, or at Pandanon where evidence of heavy blast fishing has been observed both inside and outside the MPA (Bayley et al 2019). While small MPAs can be effective for the protection of mobile species (Claudet et al 2010), the observed declines of larger fish in this study could also indicate an important limitation to these very small areas, which are typically less than the 2 km minimum diameter suggested for even partial protection of most reef fishes (Krueck et al 2017). The declines indicate the need for larger reserves which fully capture species' home ranges and for wider fisheries management in this area in order to fully protect stocks.…”
Section: Benthic Community Compositionmentioning
confidence: 63%